An unusual retinal vascular morphology in connection with a novel AIPL1 mutation in Leber's congenital amaurosis. Issue 8 (24th July 2003) - Heegaard, S; Rosenberg, T; Preising, M; Prause, J U; Bek, T
Abstract : Aims: To report a case of an unusual retinal vascular morphology in connection with a novel AIPL1 mutation in a patient with Leber's congenital amaurosis (LCA). Methods: A patient with LCA and no light perception from birth had both eyes enucleated at the age of 22 years because of excruciating pain. Mutation analysis was performed on known LCA genes. The eyes were processed for casts of the vascular tree, routine histopathology, and electron microscopy. Results: A novel H82Y (244C→T) mutation and a H90D (286G→C) polymorphism were detected in exon 2 of the AIPL1 gene. Both the cast and the histopathological examination showed dilated retinal vessels, mainly venules, primarily localised in the posterior pole. In the mid-peripheral retina the density of capillaries on the arteriolar side of the microcirculatory units was significantly decreased. The vascular system was seen to gradually attenuate towards the retinal periphery, and to stop at a zone located approximately 4 mm from the ora serrata along the whole circumference. In this zone pigmented aggregates characteristic of retinitis pigmentosa were seen to ensheath the retinal vessels. The photoreceptors were almost totally absent and retinal gliosis was present. A decreased number of ganglion cells and an increased vacuolisation of the nerve fibre layer were observed. The retinal pigment cells and Bruch's membrane appeared normal in all regions. Conclusion: An unusual retinal vascular morphology in an LCA patient is presented and possible pathogenic mechanisms of the findings are discussed.